Hybrid vehicular communications - Jooriah, Mohannad (2022)
Vehicle Communications is a promising research field, with a great potential for the development of new applications capable of improving road safety, traffic efficiency, as well as passenger comfort and infotainment. Vehicle communication technologies can be short-range, such as ETSI ITS-G5 or the 5G PC5 sidelink channel, or long-range, using the cellular network (LTE or 5G). However, none of the technologies alone can support the expected variety of applications for a large number of vehicles, nor all the temporal and spatial requirements of connected and autonomous vehicles. Thus, it is proposed the collaborative or hybrid use of short-range communications, with lower latency, and of long-range technologies, potentially with higher latency, but integrating aggregated data of wider geographic scope. In this context, this work presents a hybrid vehicle communications model, capable of providing connectivity through two Radio Access Technologies (RAT), namely, ETSI ITS-G5 and LTE, to increase the probability of message delivery and, consequently, achieving a more robust, efficient and secure vehicle communication system. The implementation of short-range communication channels is done using Raw Packet Sockets, while the cellular connection is established using the Advanced Messaging Queuing Protocol (AMQP) protocol. The main contribution of this dissertation focuses on the design, implementation and evaluation of a Hybrid Routing Sublayer, capable of isolating messages that are formed/decoded from transmission/reception processes. This layer is, therefore, capable of managing traffic coming/destined to the application layer of intelligent transport systems (ITS), adapting and passing ITS messages between the highest layers of the protocol stack and the available radio access technologies. The Hybrid Routing Sublayer also reduces the financial costs due to the use of cellular communications and increases the efficiency of the use of the available electromagnetic spectrum, by introducing a cellular link controller using a Beacon Detector, which takes informed decisions related to the need to connect to a cellular network, according to different scenarios. The experimental results prove that hybrid vehicular communications meet the requirements of cooperative intelligent transport systems, by taking advantage of the benefits of both communication technologies. When evaluated independently, the ITS-G5 technology has obvious advantages in terms of latency over the LTE technology, while the LTE technology performs better than ITS-G5, in terms of throughput and reliability.